Clinical Determinants for Successful Circulating Tumor DNA Analysis in Prostate Cancer - Schweizer, Michael T. (Prostate, 2019)
BACKGROUND: Plasma-based cell-free DNA is an attractive biospecimen for assessing somatic mutations due to minimally-invasive real-time sampling. However, next generation sequencing (NGS) of cell-free DNA (cfDNA) may not be appropriate for all patients with advanced prostate cancer (PC). METHODS: Blood was obtained from advanced PC patients for plasma-based sequencing. UW-OncoPlex, a ~2Mb multi-gene NGS panel performed in the CLIA/CAP environment, was optimized for detecting cfDNA mutations. Tumor tissue and germline samples were sequenced for comparative analyses. Multivariate logistic regression was performed to determine the clinical characteristic associated with the successful detection of somatic cfDNA alterations (i.e. detection of at least one clearly somatic PC mutation). RESULTS: Plasma for cfDNA sequencing was obtained from 93 PC patients along with tumor tissue (N=67) and germline (N=93) controls. We included data from 76 patients (72 prostate adenocarcinoma; 4 variant histology PC) in the analysis. Somatic DNA aberrations were detected in 34 cfDNA samples from patients with prostate adenocarcinoma. High PSA level, high tumor volume, and castration-resistance were significantly associated with successful detection of somatic cfDNA alterations. Among samples with somatic mutations detected, the cfDNA assay detected 93/102 (91%) alterations found in tumor tissue, yielding a clustering-corrected sensitivity of 92% (95% confidence interval 88%–97%). All germline pathogenic variants present in lymphocyte DNA were also detected in cfDNA (N=12). Somatic mutations from cfDNA were detected in 30/33 (93%) instances when PSA was >10ng/ml. CONCLUSIONS: Disease burden, including a PSA >10ng/ml, is strongly associated with detecting somatic mutations from cfDNA specimens.